2011
DOI: 10.1186/1477-7827-9-34
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of unilateral sectioning the superior ovarian nerve of rats with unilateral ovariectomy on ovarian hormones (progesterone, testosterone and estradiol) levels vary during the estrous cycle

Abstract: The present study analyzed the participation of the left and right superior ovarian nerves (SON) in regulating progesterone, testosterone, and estradiol serum levels in unilaterally ovariectomized rats on each day of the estrous cycle. For this purpose, ovarian hormone concentrations in serum were measured in animals with either sham-surgery, unilateral ovariectomy (ULO), unilateral sectioning of the SON, or sectioning of the SON innervation of the in situ ovary in rats with ULO.This investigation results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 54 publications
4
21
0
Order By: Relevance
“…As previously proposed for adult animals [19,23], the results obtained in the present study suggest that the SON innervation arriving to the ovaries of pre-pubertal rats plays a role regulating P 4 , T, and E 2 secretion. However, there is a difference between pre-pubertal and adult animals in their hormone secretion ability, suggesting that in the pre-pubertal stage of the animal the neural, and even perhaps the hormone regulation system, is not mature.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As previously proposed for adult animals [19,23], the results obtained in the present study suggest that the SON innervation arriving to the ovaries of pre-pubertal rats plays a role regulating P 4 , T, and E 2 secretion. However, there is a difference between pre-pubertal and adult animals in their hormone secretion ability, suggesting that in the pre-pubertal stage of the animal the neural, and even perhaps the hormone regulation system, is not mature.…”
Section: Discussionsupporting
confidence: 88%
“…However, there is a difference between pre-pubertal and adult animals in their hormone secretion ability, suggesting that in the pre-pubertal stage of the animal the neural, and even perhaps the hormone regulation system, is not mature. Another possibility that may explain such difference is the time of the day when the animals were treated (9:00–11:00 in pre-pubertal animals and 13:00 h in adult) [23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of unilateral or bilateral laparotomy on progesterone, testosterone and estradiol serum levels depend on the day of the cycle and the surgical approach (dorsal or ventral) used [84][85][86][87][88][89].…”
Section: The Participation Of the Ovarian Innervations In Regulating mentioning
confidence: 99%
“…The contribution of circulating T to the control of female reproductive function is of particular interest since previous studies have shown that circulating levels of this steroid in females are higher than those of E 2 and fluctuate several-fold across the ovarian cycle [9,10]. In female primates, circulating androgens contribute significantly to the expression of sexual behavior and the regulation of reproductive function [11,12].…”
Section: Introductionmentioning
confidence: 99%